2007
DOI: 10.1109/vetecs.2007.108
|View full text |Cite
|
Sign up to set email alerts
|

A Markov Model for MIMO Channel Condition Number with Application to Dual-Mode Antenna Selection

Abstract: Abstract-The condition number is a well known indicator of the spatial selectivity of a MIMO wireless channel. The objective of this paper is to examine the temporal behavior of this metric using a Markov model construction. Specifically, we have developed two methods to calculate analytically the transition probabilities between Markov states. These methods involve the joint density for the channel eigenvalues at two adjacent time instances and the level crossing rates (LCR) of the condition number. We then u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Therefore, it is possible to define log K k = instead of k , which can be approximated by a gamma random variable [10]. Based on the preceding discussion in the section, SM is selected if K is less than or equal to the threshold 2 min, 2 min,…”
Section: B Markov Model Of the Channel Condition Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is possible to define log K k = instead of k , which can be approximated by a gamma random variable [10]. Based on the preceding discussion in the section, SM is selected if K is less than or equal to the threshold 2 min, 2 min,…”
Section: B Markov Model Of the Channel Condition Numbermentioning
confidence: 99%
“…Here, the derivation of the LCR for K is epitomized, however a more complete version is offered in [10]. Because the distribution of K can be very accurately approximated by a gamma variable, the LCR formula for the gamma process is given by:…”
Section: B Markov Model Of the Channel Condition Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…However, his analysis was limited to the case of (2 × 2) central Wishart matrices with unit variance where the generalized work of Ratnarajah et al [9] accounted for matrices of random size and with arbitrary variance. An interesting approach to model the temporal transition probabilities of the condition number using a finite-state Markov process can be found in [10]; more importantly, it was shown that the CDF of the logarithm of the condition number can be approximated particularly well via a gamma variable. Yet, all the above cited papers ( [8]- [10]) were limited to Rayleighfading MIMO channels while the extension to Ricean-fading channels remains an open problem.…”
mentioning
confidence: 99%
“…An interesting approach to model the temporal transition probabilities of the condition number using a finite-state Markov process can be found in [10]; more importantly, it was shown that the CDF of the logarithm of the condition number can be approximated particularly well via a gamma variable. Yet, all the above cited papers ( [8]- [10]) were limited to Rayleighfading MIMO channels while the extension to Ricean-fading channels remains an open problem. On this basis, in the present study we explore the statistics of the condition number of a dual non-central Wishart matrix and introduce closedform formulae for its PDF and CDF as weighted sums of polynomials.…”
mentioning
confidence: 99%